Chronic exposure to low-dose of X-rays induces DNA double-strand breaks in mammalian cells - Grillo, Claudia Alejandra (2011)
The purpose of present study is to evaluate the induction of clastogenic effect after chronic exposure to low dose of ionising radiation in both CHO-K1 cells and in their DNA Double-Strand Breaks (DSBs)-repair deficient mutant xrs-5. Cells were cultured for 14 dilution cycles and grown to confluency. Radiation treatment was performed once per cycle with 10 mGy X-rays to carry out the structural chromosome aberration test. The results showed a significant increase in the frequency of achromatic lesions (p < 0.001) in CHO-K1 cells. In addition, xrs-5 cells showed an increase of chromatid and chromosome-type aberrations (p < 0.001). Sequential exposure produced a level of DNA damage that is amplified through successive cycles triggering the efficient repair of DSBs. The increased damage in xrs-5 cells provides evidence that the non-homologous end-joining repair of DNA DSBs is involved after low dose X-ray exposure.